(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explore the role of the free association technique in psychoanalysis as a tool to measure and understand the level of individual consciousness Free association, introduced by Sigmund Freud, is a method in which individuals are asked to express thoughts, feelings, and associations that arise without censorship. Through this approach, researchers seek to identify patterns that appear in the subconscious mind that can influence individual behavior and awareness. This study uses a qualitative method with in-depth analysis of the transcript of therapy sessions involving free association techniques. The results of the study show that free association not only helps individuals in expressing internal conflicts, but also provides deeper insights into the structure of their consciousness. These findings are expected to make a significant contribution to the understanding of clinical psychology and psychoanalytic practice, as well as pave the way for the development of more effective therapeutic techniques in increasing individual self-awareness. Thus, this study emphasizes the importance of free association as a diagnostic and therapeutic tool in the context of psychoanalysis